Annual Plan 1971-72 Part II-Statements Government of Maharashtra - Planning Commission (Planning Commission, 1971)
List of Schemes Included In The State Plan Abstract Statement Showing Outlays Included In The Annual Plan, 1971-72. Detailed Statement of Schemes Included Detailed Statement of Schemes Included Abstract Statement Showing Outlay Included In The Annual Plan, 1971-72 Centrally Sponsored (Central Plan) Detailed Statement of Schemes Included In The Centrally Sponsored (Central Plan) Programme, 1971-72 Annual Plan 1971-72 Targets and Achievements For Selected Programmes.
Government of Maharashtra Finance Department (Planning)